Loneliness in vietnamese and russian students: scale validation and cross-cultural comparisons - Tran, T.C. (Socialʹnaâ Psihologiâ i Obŝestvo, 2025)
Abstract only Context and relevance. How loneliness is perceived, experienced, and expressed can vary significantly across cultures due to differences in social norms, values, and interpersonal expectations. Therefore, it is crucial to adapt measurement tools to reflect these cultural variations and ensure their relevance. In this regard, the De Jong Gierveld Loneliness Scale is a widely recognized tool for assessing loneliness. However, it requires cultural adaptation and validation to ensure it accurately measures loneliness in diverse cultural contexts.Objective. The study aims to evaluate the psychometric properties of the De Jong Gierveld Loneliness Scale, specifically examining its factor structure, reliability, and measurement invariance among university students in Vietnam and Russia. Methods and materials. A total of 242 Vietnamese and 216 Russian students completed the scale. Exploratory factor analysis and confirmatory factor analysis were conducted separately for each group to confirm the factor structure. Cronbach's alpha assessed reliability, and measurement invariance testing determined whether the scale functioned equivalently across cultures. Latent profile analysis identified loneliness subgroups within each sample. Results. A two-factor structure (1) emotional loneliness and (2) social loneliness was confirmed in both groups. The scale showed configural (CFI = 0,953), metric (ΔCFI = 0,004), and scalar invariance (ΔCFI = 0,005) across groups, indicating measurement equivalence, though strict invariance was not supported (ΔCFI = 0,012). Latent profile analysis revealed distinct loneliness profiles which is a demonstration of the scale's ability to differentiate groups with different characteristics. Reliability was acceptable (αVietnam = 0,78; αRussia = 0,84). Conclusions. The adapted scale demonstrated good psychometric properties in Vietnamese and Russian. Контекст и актуальность. Способы восприятия, переживания и выражения одиночества могут существенно различаться в разных культурах из-за различий в социальных нормах, ценностях и межличностных ожиданиях. Поэтому крайне важно адаптировать инструменты измерения состояния одиночества с учетом этих культурных различий. Шкала одиночества Де Йонга Гирвельда является широко признанным инструментом для оценки этого состояния. Однако она требует культурной адаптации и валидизации, чтобы обеспечить точное измерение состояния одиночества в различных культурных контекстах. Цель. Оценка психометрических свойств шкалы одиночества Де Йонга Гирвельда, в частности, изучение ее факторной структуры, надежности и неизменности измерений среди студентов университетов Вьетнама и России. Методы и материалы. В исследовании приняли участие 242 вьетнамских и 216 российских студентов, которые заполнили шкалу. Для подтверждения факторной структуры проводился отдельный исследовательский и подтверждающий факторный анализ для каждой группы. Надежность оценивалась с помощью альфа Кронбаха, а тестирование измерительной инвариантности позволило определить, функционирует ли шкала одинаково в разных культурах. Латентный профильный анализ выявил подгруппы одиночества в каждой выборке. Результаты. В обеих группах была подтверждена двухфакторная структура: (1) эмоциональное одиночество и (2) социальное одиночество. Шкала продемонстрировала конфигурационную (CFI = 0,953), метрическую (ΔCFI = 0,004) и скалярную инвариантность (ΔCFI = 0,005) между группами, что указывает на эквивалентность измерений, однако строгая инвариантность не была поддержана (ΔCFI = 0,012). Латентный профильный анализ выявил различные профили одиночества, демонстрируя способность шкалы различать группы с разными характеристиками. Надежность шкалы была удовлетворительной (αВьетнам = 0,78; αРоссия = 0,84). Выводы. Адаптированная шкала показала хорошие психометрические свойства среди студентов Вьетнама и России.